Keraguan Seputar Mushaf Al-Qur'an: Kajian Resepsi terhadap Manuskrip Birmingham - Faizin, Nur (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
The finding of the Qur’anic manuscript in Birmingham in July 2015 has surprised many people, especially Muslims and the researchers of the Qur’an. This paper discusses the reception of the manuscript using a theory of reception in the study of language and literature which allows researcher to read the corrupt text using aesthetic, textual and semiotic approach. This study is a library research and the data were collected from internet, books, etc. using documentation method. The analysis and explanation would be performed simultaneously using descriptive and qualitative method. By doing so, it is concluded that the fragment found in Birmingham has received diverse and even contradictive receptions, i.e. the receptions that strengthen the faith of the authenticity of the Qur’an and the receptions that cast doubts about. Such doubts as whether the Qur’an was God’s word to Gabriel then to Muhammad; whether the manuscript was completed in the time of Uthman or after his era; and whether Muhammad and his Companions have exploited the teachings of religion for political goals and interests. These doubts really opposed against the ideology which has long been believed as true in Islam, and it is even against the Qur’an itself. Keywords Qur’an, manuscript, Birmingham, reception, doubts.